EFEKTIVITAS METODE GASING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN DAN PEMBAGIAN BILANGAN BULAT - Yenni Buknoni; Wahyudin Wahyudin; Sandi Budi Iriawan (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to determine the effectiveness of the GASING method in improving the conceptual understanding of multiplication and division of integers among seventh-grade students at SMP Negeri 3 Kota Kupang. The study employed a quasi-experimental design with a pretest-posttest control group design. The research subjects consisted of 62 students divided into an experimental group (31 students of class VII-A) taught using the GASING method and a control group (31 students of class VII-J) taught using direct instruction. Data were collected using a conceptual understanding test.  Data analysis used descriptive statistics, normality test, homogeneity test, and independent sample t-test with the assistance of SPSS. The findings of this study demonstrate that the GASING method is proven effective in improving students’ conceptual understanding of multiplication and division of integers. This is evidenced by the mean N-gain of the experimental group of 0.83 (high category), which is higher than the control group of 0.63 (moderate category). The independent sample t-test showed a value of t = 3.879 with a significance of 0.001 (p<0.05). Cohen’s d effect size of 0.985 indicates a very large practical impact. It is concluded that the GASING method is more effective in improving conceptual understanding of multiplication and division of integers compared to direct instruction.